Beyond the Stigma of War: Russian Migrants in Kazakhstan's Labour Market - Kanat Abdulla; Evangelos Mourelatos (Global Labor Organization (GLO), 2024)
In this study, we investigate the employers' attitude towards Russian migrants in Kazakhstan's labor market. We conduct a field experiment by sending over 1600 fictitious job applications to real job openings posted on one of the largest job search portals in the country. The job applicants included a local Kazakh, a local Russian, a migrant from Kyrgyzstan, and a migrant from Russia. We found significant differences in employment outcomes across ethnic groups in the selected occupations. Specifically, Russian migrants were significantly less likely to receive an interview invitation. Interestingly, sympathy towards Russian applicants was weakest for occupations located more than 830 km from the Russian borders and those requiring high-skilled workers. Our findings provide evidence for less favorable attitudes towards migrant workers from Russia during the Russia-Ukraine conflict.
Keywords: C93; J71; J78; J64; 330; discrimination; labour market; migrant workers; field experiment